2020
DOI: 10.11648/j.ajam.20200804.14
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and Heat Source Effects on MHD Free Convection Flow over an Inclined Porous Plate in the Presence of Viscous Dissipation

Abstract: This study analyzes radiation, viscous dissipation and heat source effects on magneto-hydrodynamic free convection flow, of a viscous incompressible fluid over an inclined porous plate. Applying the perturbation technique, the solution of a set of ordinary differential equations are gotten as a result of reducing the non-linear partial differential equations of motion, energy and diffusion, which is solved analytically for velocity, temperature and the concentration distribution. The effect of Radiation, visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Indications from their findings depicts that rate of fluid motion suppresses as temperature and concentration elevates. Studies abound on the influence of thermal radiation on fluid flows and the results obtained have been significant, (Raptis et al, 2004), (Mabood et al, 2017), (Devi and Reddy, 2014), (Bunonyo et al, 2018) and (Omamoke et al, 2020) just to mention but a few. However, influence of radiation, viscosity on MHD non-steady natural flow past a partially sieve-like material was analyzed by (Joaquin, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Indications from their findings depicts that rate of fluid motion suppresses as temperature and concentration elevates. Studies abound on the influence of thermal radiation on fluid flows and the results obtained have been significant, (Raptis et al, 2004), (Mabood et al, 2017), (Devi and Reddy, 2014), (Bunonyo et al, 2018) and (Omamoke et al, 2020) just to mention but a few. However, influence of radiation, viscosity on MHD non-steady natural flow past a partially sieve-like material was analyzed by (Joaquin, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MHD fluids is also useful in various fields such as asthma treatment, tumor therapy, plasmas, Xray radiation, electrolytes biomedicine, sterilized devices and gastric medications [19]. Awasthi [20] carried out investigation on the effects of heat and mass flux on MHD free convection flow through a porous medium with radiation and first order chemical reaction. Interaction of radiation and heat source effects on MHD free convection flow over an inclined porous plate in the presence of viscous dissipation was studied by Omamoke et al [21].…”
Section: Introductionmentioning
confidence: 99%
“…Significance of viscous dissipation on MHD free convective fluid flow through inclined porous plate was considered by Rajakumar et al 17,18 Rajakumar et al 19 considered viscous dissipation and Dufour effects on MHD free convection fluid flow through a vertical Oscillatory porous plate with ion-slip current and radiation absorption. Omamoke et al, 20 Srinivasa Raju et al, 21 Suneetha et al, 22 Jithender Reddy et al, 23 Sivaiah et al, 24 Rajakumar et al, 25 and Rao et al 26 explained the significance of viscous dissipation on MHD fluid past a vertical porous plate. Rajakumar et al 27 reported the impact of viscous dissipation on MHD flow over a fluctuating nonparallel porous plate in presence of chemical reaction along with radiation absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Substituting Equation (20) in Equations ( 15)-( 17) and omitting the larger power terms o ε ( ) 2 , then it was obtained:…”
Section: Introductionmentioning
confidence: 99%